Regional per Capita-Income - The Importance of Region-Specific Production Factors - Dirk Fornahl; Axel Johannes Schaffer; Jochen Siegele (Swiss Journal of Economics and Statistics, 2009)
Endowment with infrastructure, human and cultural capital is highly significant for regional economic performance. After clustering the regions, this hypothesis is tested for Austrian, German and Swiss NUTS 3 regions by applying a quantile regression analysis. First results confirm the hypothesis for all factors. However, coefficients differ significantly both between clusters as well as among the quantiles of each cluster. Furthermore, insights into the regions' efficiency in using these factors are generated: investments into region-specific factors will not push the regional economy automatically, but the under- or above-average efficiency has to be taken into account.
Keywords: C12; H54; O15; O18; Z10; 330; Quantile regression; regional efficiency; infrastructure; human capital; cultural capital